Baltic Sea coastal erosion; a case study from the Jastrzębia Góra region - Uścinowicz, Grzegorz; Kramarska, Regina; Kaulbarsz, Dorota; Jurys, Leszek; Frydel, Jerzy; Przezdziecki, Piotr; Jegliński, Wojciech (Geologos, 2015)
The coastline in the Jastrzębia Góra area can be divided into three major zones of general importance: a beach and barrier section, a cliff section, and a section protected by a heavy hydrotechnical construction. These areas are characterised by a diverse geology and origin, and hence different vulnerability to erosion. In addition, observations have demonstrated a different pace of erosion within each zone. Based on the results obtained by remote sensing methods (analysis of aerial photographs and maps), it has been determined that the coastline in the barrier area, i.e., to the west of Jastrzębia Góra, moved landwards by about 130 m, in a period of 100 years, and 80 m over about 50 years. A smaller displacement of the shoreline could be observed within the cliff. Between the middle of the twentieth and the start of the twenty-first centuries the shore retreated by about 25 m. However, in recent years, an active landslide has led to the displacement of the uppermost part of the cliff locally up to 25 m. Another issue is, functioning since 2000, a heavy hydrotechnical construction which has been built in order to protect the most active part of the cliff. The construction is not stable and its western part, over a distance of 50 m, has moved almost 2 m vertically downwards and c. 2.5 m horizontally towards the sea in the past two years. This illustrates that the erosional factor does not comprise only marine abrasion, but also involves land-based processes determined by geology and hydrogeology. Changes in the shoreline at the beach and barrier part are constantly conditioned by rising sea levels, the slightly sloping profile of the sea floor and low elevation values of the backshore and dune areas. Cliffs are destroyed by mass wasting and repetitive storm surges that are responsible for the removal of the colluvium which protects the coast from adverse wave effects. Presumably, mass movements combined with groundwater outflow from the cliff, plus sea abrasion cause destabilisation of the cliff protection construction.